Implementasi Pengetahuan Green Economy, Employability Skills, Dan Maqashid Syariah Terhadap Minat Karir Karyawan Yang Dimoderasi Oleh Dukungan Terhadap Sustainable Development Goals - Zayda Vindhya Adhisya; Uus Rustiman; Cupian; Yudi Ahmad Faisal (Jurnal Ilmiah Ekonomi Islam, 2026)
This study aims to analyze the influence of green economy knowledge, employability skills, and maqashid sharia on employee career interest, with support for the Sustainable Development Goals (SDGs) as a moderating variable. This study used a quantitative approach with a survey method. Respondents were employees of the Wholesale Services Division – Managed Service Quality Operation, PT. Telkom Indonesia. The data analysis technique used Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results showed that green economy knowledge, employability skills, and maqashid sharia did not significantly influence employee career interest. Furthermore, support for the SDGs was also not proven to strengthen the relationship between the independent and dependent variables. These findings suggest that employee career interest in organizations with structured career systems is more influenced by factors other than the knowledge, skills, and values ​​studied. This research is expected to contribute to the development of studies on career interest and sustainability in an organizational context.